MEDICO-GENETIC ASPECTS OF INFERTILITY - N. N. Goncharova; E. Yu. Martyshkina; T. V. Kaznacheyeva; K. N. Arslanyan; L. V. Adamyan; L. F. Kurilo; T. M. Sorokina; V. F. Chernych (IRBIS LLC, 2016)
Results of medico-genetic examination of 304 married couples with infertility (608 individuals) are presented in article. Frequency of genetic abnormalities and infertility structure are revealed. Comparative analysis between 2 groups of couples with male as well as combined infertility is performed. The groups were formed according the results of infertility treatment using methods of ART. The factors having had statistically significant impact on fertility were revealed.